The rise and fall of the Soviet Union [videorecording] - Baake, Franz; Graves, Peter; Nussabaum, Raphael; Rosinski, Peter ([S.l.] North Hollywood Calif. Delta Unique Media VCII Home Entertainment [distributor], 1992)
An epic film that clearly sets forth the dramatic events which occured before during and after the Russian Revolution. It takes the viewer through the First and Second World Wars, the Cold War and through the crumble and collapse of Russia.
VHS.
Hosted and narrated by Peter Graves; additional narration by Michael P. Slater; edited by Patrick Flannery and Erica Von Stagmann; historical and political research by Fritjof Merger and Edward Laton Fuller.
Keywords: Soviet Union -- History; Soviet Union -- History -- 20th century; Soviet Union -- Politics and government -- 1945-1991.; Europe, Eastern -- Politics and government -- 1945-1989.; EUROPEAN HISTORY; POLITICAL SCIENCE